2022
DOI: 10.3390/genes13071158
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Genetic and Non-Genetic Cardiovascular Risk Factors in Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is the most common monogenic metabolic disorder characterized by considerably elevated low-density lipoprotein cholesterol (LDL-C) levels leading to enhanced atherogenesis, early cardiovascular disease (CVD), and premature death. However, the wide phenotypic heterogeneity in FH makes the cardiovascular risk prediction challenging in clinical practice to determine optimal therapeutic strategy. Beyond the lifetime LDL-C vascular accumulation, other genetic and non-genetic risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 132 publications
0
6
0
1
Order By: Relevance
“…While these risk stratifications could be integrated into the clinical practice of HeFH, future investigation is needed to determine if other elements of risk stratification could improve HeFH outcomes. Therefore, in addition to LDL-C, evidence for other potential cardiovascular risk factors in patients with FH is also emerging [12]. Several former observations in HeFH populations failed to find associations between LDL-C and atherosclerotic cardiovascular events and indicated that other lipoprotein fractions and inflammatory cytokines might be strong driving factors of cardiovascular risk in the HeFH population [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these risk stratifications could be integrated into the clinical practice of HeFH, future investigation is needed to determine if other elements of risk stratification could improve HeFH outcomes. Therefore, in addition to LDL-C, evidence for other potential cardiovascular risk factors in patients with FH is also emerging [12]. Several former observations in HeFH populations failed to find associations between LDL-C and atherosclerotic cardiovascular events and indicated that other lipoprotein fractions and inflammatory cytokines might be strong driving factors of cardiovascular risk in the HeFH population [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The lifetime cardiovascular risk of individuals with untreated heterozygous FH (HeFH) was estimated to be 3.9-fold greater than that of non-FH subjects [10]. This risk not only depends on the type of molecular defect of the canonical genes and consequent LDL-cholesterol (LDL-C) concentrations, but also on the presence of other traditional and non-traditional/novel risk biomarkers [11,12]. Since HeFH is characterized by severe hypercholesterolemia and enhanced atherogenesis, HeFH can be a suitable target population for examining serum SDF-1.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have unveiled that inhibition of ORP7 leads to an increase in ABCA1 dependent cholesterol efflux to apolipoprotein A1 (ApoA1) in kidney podocytes, while ORP7 inhibition had a weaker impact on cholesterol efflux to high-density lipoprotein (HDL) particles (9). A whole genome sequencing study in a Malaysian cohort showed that participants with a ORP7 c.651_652del variant had 17 times higher odds of hypercholesterolemia than subjects without the variant (10). A large-scale study of the human macroautophagy pathway revealed that ORP7 among other ORPs binds to the unlipidated form of LC3B and is required for macroautophagy (11).…”
Section: Introductionmentioning
confidence: 99%
“…A variable proportion of measured LDL‐C derives from lipoprotein(a) [Lp(a)] that, contains apolipoprotein B‐100 [apoB100] attached via disulfide bond to the hydrophilic, highly glycosylated apolipoprotein(a) [apo(a)] 5 . The remaining cases are attributed to unspecified genetic and exogenous factors 6 …”
Section: Introductionmentioning
confidence: 99%
“…5 The remaining cases are attributed to unspecified genetic and exogenous factors. 6 The most common monogenic cause for FH are variants in the low-density-lipoprotein receptor (LDLR) gene (80%-90%). To date, the variant database ClinVar lists over 2000 disease-causing LDLR variants.…”
Section: Introductionmentioning
confidence: 99%